Early career teachers' sense of professional agency in the classroom: associations with turnover intentions and perceived inadequacy in teacher–student interaction. Issue 3 (27th May 2017) - Heikonen, Lauri; Pietarinen, Janne; Pyhältö, Kirsi; Toom, Auli; Soini, Tiina
ABSTRACT: Teachers' capacity to learn intentionally and responsively in the classroom is particularly vulnerable during the first years in the profession. This study investigated the interrelations between early career teachers' turnover intentions, perceived inadequacy in teacher–student interaction, and sense of professional agency in the classroom. The survey data were collected from 284 in-service teachers with not more than 5 years of experience and analysed by structural equation modelling (SEM). The results showed that the negative relation between turnover intentions and early career teachers' sense of professional agency was completely mediated by perceived inadequacy in teacher–student interaction. The results indicate that experiences of insufficient abilities to solve pedagogically and socially challenging student situations have a crucial effect on early career teacher's capacity for adaptive reflection and active transformation of instruction.